Improving the cost-effectiveness of a healthcare system for depressive disorders by implementing telemedicine: a health economic modeling study - Lokkerbol, Joran (2013)
OBJECTIVE: Depressive disorders are important causes of disease burden and are associated with substantial economic costs. Therefore, it is important to design a health care system that can effectively manage depression at sustainable costs. This paper computes the benefit-to-costs ratio of the current Dutch health care system for depression, and investigates whether offering more online preventive interventions improves the cost-effectiveness overall. METHODS: A health economic (Markov) model was used to synthesize clinical and economic evidence and to compute population-level costs and effects of interventions. The model compares a base-case scenario without preventive telemedicine and alternative scenarios with preventive telemedicine. The central outcome is the benefit-to-cost ratio, also known as return-on-investment (ROI). RESULTS: In terms of ROI, a health care system with preventive telemedicine for depressive disorders offers better value for money than a health care system without internet-based prevention. Overall, the ROI increases from €1.45 ($1.72) in the base-case scenario to €1.76 ($2.09) in the alternative scenario where preventive telemedicine is offered. In a scenario where the costs of offering preventive telemedicine are balanced by cutting back on the expenditure for curative interventions, ROI increases to €1.77 ($2.10), while keeping the health care budget constant. CONCLUSION: In order for a health care system for depressive disorders to remain economically sustainable, its cost-benefit ratio needs to be improved. Offering preventive telemedicine at a large scale is likely to introduce such an improvement.